Co‐expression analysis provides important module and pathways of human dilated cardiomyopathy. Issue 1 (24th June 2019) - Xiao, Junhui; Li, Fang; Yang, Qianzhao; Zeng, Xue‐Feng; Ke, Zun‐Ping
Abstract: Dilated cardiomyopathy (DCM) is a heart disease that injured greatly to the people wordwide. Systemic co‐expression analysis for this cancer is still limited, although massive clinic experiments and gene profiling analyses had been well performed previously. Here, using the public RNA‐Seq data "GSE116250" and gene annotation of Ensembl database, we built the co‐expression modules for DCM by Weighted Gene Co‐Expression Network Analysis, and investigated the function enrichment and protein‐protein interaction (PPI) network of co‐expression genes of each module by Database for Annotation, Visualization, and Integrated Discovery and Search Tool for the Retrieval of Interacting Genes/Proteins database, respectively. First, 5, 000 genes in the 37 samples were screened and 11 co‐expression modules were conducted. The number of genes for each module ranged from 77 to 936, with a mean of 455. Second, interaction relationships of hub‐genes between pairwise modules showed great differences, suggesting relatively high‐scale independence of the modules. Third, functional enrichments of the co‐expression modules exhibited great differences. We found that genes in module 3 were significantly enriched in the pathways of focal adhesion and ubiquitin‐mediated proteolysis. This module was inferred as the key module involved in DCM. In addition, PPI analysis revealed that the genes HSP90AA1, CTNNB1, MAPK1, GART, and PPP2CA owned the largest number of adjacency genes, unveiling that they may function importantly during the occurrence of DCM. Focal adhesion and ubiquitin‐mediated proteolysis play important roles in human DCM. Abstract : The hub genes HSP90AA1, CTNNB1, MAPK1, GART, and PPP2CA were found to be significantly enriched in module 3, which may be potential biomarkers in diagnostic and prognostic for dilated cardiomyopathy (DCM).